Population ecology of Jujubinus striatus and Jujubinus exasperatus (Gastropoda: Trochidae) in a Posidonia oceanica seagrass bed - L. Donnarumma; R. Bruno; A. Terlizzi; G. F. Russo (The European Zoological Journal, 2018)
The population structure of Jujubinus striatus and Jujubinus exasperatus (Trochidae), common gastropod grazers of Posidonia oceanica leaves, was investigated in the seagrass bed off Lacco Ameno of Ischia (Gulf of Naples). Sampling was performed monthly, from July 1981 to June 1982, at five stations along a depth gradient (1, 3, 10, 15 and 25 m), using a hand-towed net. Throughout the study period, both populations were characterised by seasonal fluctuations in abundance, with a total of 550 individuals counted and measured. The two populations analysed showed different distributional trends along the depth gradient. Jujubinus striatus settled and occurred mainly at shallower stands (1–3 m depth), while J. exasperatus was found deeper (10–15 m). Both species are semelparous. Juveniles and small individuals (shell height < 4 mm) were mainly found during the late winter and early spring months. The survivorship curves of both Jujubinus species showed a very low mortality rate in the first few months after settlement. Demographic analysis suggests an indeterminate growth rate after sexual maturity, with a lifespan of about 22 months for J. striatus and 17 months for J. exasperatus. For both species the growth rate is fast during the first couple of months after settlement. The findings of this study, compared with earlier work, reveal a certain number of shared traits in the life cycle of the most common gastropod species living on the leaves of P. oceanica seagrass: semelparous reproduction, spring settlement, fast early growth and short lifespan (2 years maximum).